Estrogen receptor activation by tobacco smoke condensate in hormonal therapy-resistant breast cancer cells. Issue 165 (January 2017) - Niwa, Toshifumi; Shinagawa, Yuri; Asari, Yosuke; Suzuki, Kanae; Takanobu, Junko; Gohno, Tatsuyuki; Yamaguchi, Yuri; Hayashi, Shin-ichi
Highlights: Effect of tobacco smoke condensate on estrogen receptor activity was examined. TSC significantly activated ERs, and upregulated its endogenous target genes. ER activation was inhibited by fulvestrant and weakly inhibited by tamoxifen. TSC activates ER by both ligand-dependent and – independent mechanisms. Tobacco smoke may interfere with hormonal therapy for breast cancer. Abstract: The relationship between tobacco smoke and breast cancer incidence has been studied for many years, but the effect of smoking on hormonal therapy has not been previously reported. We investigated the effect of smoking on hormonal therapy by performing in vitro experiments. We first prepared tobacco smoke condensate (TSC) and examined its effect on estrogen receptor (ER) activity. The ER activity was analyzed using MCF-7-E10 cells into which the estrogen-responsive element (ERE)-green fluorescent protein (GFP) reporter gene had been stably introduced (GFP assay) and performing an ERE-luciferase assay. TSC significantly activated ERs, and upregulated its endogenous target genes. This activation was inhibited by fulvestrant but more weakly by tamoxifen. These results suggest that the activation mechanism may be different from that for estrogen. Furthermore, using E10 estrogen depletion-resistant cells (EDR cells) established as a hormonal therapy-resistant model showing estrogen-independent ER activity, ER activation and induction of ER target genes were significantly higher following TSC treatment than by estradiol (E2). These responses were much higher than those of the parental E10 cells. In addition, the phosphorylation status of signaling factors (ERK1/2, Akt) and ER in the E10-EDR cells treated with TSC increased. The gene expression profile induced by estrogenic effects of TSC was characterized by microarray analysis. The findings suggested that TSC activates ER by both ligand-dependent and -independent mechanisms. Although TSC constituents will be metabolized in vivo, breast cancer tissues might be exposed for a long period along with hormonal therapy. Tobacco smoke may have a possibility to interfere with hormonal therapy for breast cancer, which may have important implications for the management of therapy.